Three‐dimensional evaluation of upper airway in patients with different anteroposterior skeletal patterns. (26th August 2013) - Zheng, Z. H.; Yamaguchi, T.; Kurihara, A.; Li, H. F.; Maki, K.
Structured Abstract Objectives To investigate variability in the upper airway of subjects with different anteroposterior skeletal patterns by evaluating the volume and the most constricted cross‐sectional area of the pharyngeal airway and defining correlations between the different variables. Material and methods The study sample consisted of 60 patients (29 boys, 31 girls) divided into three groups: Class I (1 ≤ ANB≤3), Class II (ANB>3), and Class III (ANB<1), to evaluate how the jaw relationship affects the airway volume and the most constricted cross‐sectional area (Min‐CSA). Differences between groups were determined using the Tukey–Kramer test. Correlations between variables were tested using Pearson's correlation coefficient. Results The volume and the Min‐CSA of the pharyngeal airway (PA) were significantly related to anteroposterior skeletal patterns (p < 0.05). The nasopharyngeal airway (NA) volume of Class I and Class III subjects was significantly larger than that of Class II subjects (p < 0.05). The Min‐CSA and the length of PA were significantly related to the volume of PA (p < 0.05). The site and the size of the Min‐CSA varied among the three groups. Conclusions The volume and the most constricted cross‐sectional area of the airway varied with different anteroposterior skeletal patterns. The NA volume of Class I and Class III subjects was significantly larger than that of patients with a Class II skeletal pattern.